Середньострокові пріоритети бюджетної політики соціального розвитку суспільства - Качула, Світлана Валентинівна; Kachula, Svitlana (Університет митної справи та фінансів, 2019)
У статті розглянуто стан та перспективи подальшого вдосконалення впровадження середньо-строкового планування в Україні. Визначено, що запровадження середньострокового бюджетного планування дає змогу розширити можливості щодо формування середньострокових пріоритетів бюджетної політики соціального розвитку суспільства, тобто за межами річного бюджетного плану. Зазначено, що науково обґрунтована середньострокова бюджетна політика повинна враховувати вплив попередніх бюджетних зобов’язань, а також майбутні витрати на соціальний розвиток суспільства. Встановлено, що під час формування середньострокових пріоритетів бюджетної політики є потреба в попередній інформації щодо формування потенційно можливих чинників, які можуть вплинути на показники середньострокових планів. Ключову роль у формуванні середньострокових пріоритетів бюджетної політики відіграє програмно-цільовий метод формування бюджету як метод, що дає змогу оцінити ефективність та результативність витрачання бюджетних коштів. Виокремлено реальні проблеми та перешкоди щодо впровадження середньострокового бюджетування, які є викликами для забезпечення реалістичності прогнозів. The article examines the state and prospects for the medium-term planning implementation further improvement in Ukraine. The article states that medium-term budget planning allows to expand the possibilities for forming medium-term priorities of the budget policy of social development of society, that is, outside the annual budget plan. It is noted that scientifically grounded medium-term fiscal policies should reflect the impact of previous budget commitments, as well as future expenditures on social development. An effective and efficient budget process is possible through mid-term planning that helps to stabilize the budget, thus contributing to the effectiveness of budget policies. The main forecast macroeconomic indicators of economic and social development of Ukraine for 2018-2020 are analyzed. It is determined that despite the growth of the projected key macroeconomic indicators of Ukraine’s economic and social development, these are only prognostic data that are probable and may lose contact with reality because of various factors’ influence. It has been established that it’s necessary to get prior information on the formation of potential factors that may affect medium-term plans, during formation of medium-term fiscal policy priorities. A key role in implementing the medium-term priorities of budget policy is the program-targeted method, which allows assessing budget funds spending. efficiency and effectiveness. The real problems and obstacles in implementing medium-term budgeting are identified, among which there is uncertainty and unpredictability of economic dynamics, instability of socio-economic processes that are challenges to achieve realistic forecasts. The prognosis of certain items of budget revenues, such as personal income tax, value added tax and profit tax, whose revenue is decisive in shaping socio-economic indicators, play a role in medium-term forecasting of incomes. It is proved that mandatory monitoring of the formation of budget revenues and expenditures should become a necessary component of the implementation of the medium-term planning. This will foster the orientation of budget policy priorities to ensure economic and financial stability, sustainable social development of society.
Mid-term priorities of social development budget policy
Keywords: бюджетна політика; budget policy; середньострокове планування; medium-term planning; пріоритети бюджетної політики; budget policy priorities; соціальний розвиток; social development; моніторинг середньострокового прогнозу; the medi-umterm forecast monitoring